Omental Infarction: An Underrecognized Cause of Right-Sided Acute Abdominal Pain in Children. Issue 12 (8th December 2021) - Di Nardo, Giovanni; Di Serafino, Marco; Gaglione, Giovanni; Mercogliano, Carmela; Masoni, Luigi; Villa, Maria Pia; Parisi, Pasquale; Ziparo, Chiara; Vassallo, Francesca; Evangelisti, Melania; Vallone, Gianfranco; Esposito, Francesco
Abstract : Supplemental digital content is available in the text. Abstract : Objective: To evaluate the prevalence of omental infarction (OI) in children with suspected appendicitis, the role of ultrasonography (US) in its diagnosis and management and the efficacy of conservative management. Methods: Consecutive children with suspected acute appendicitis were prospectively enrolled. Ultrasonography was performed at baseline, during follow-up, before the discharge, and at 15-day intervals until US findings of OI disappeared. All children with a diagnosis of OI were treated conservatively. Results: One hundred ninety-nine children (91 male; age range, 3–15 years) were evaluated. Eighty-four patients had acute appendicitis. Omental infarctions were found in 14 children (8 male; mean age, 9.8 ± 2.6 years), with an incidence of 7%. Ultrasonography depicted an echogenic mass consistent with OI in all children. Ultrasonography detected in 8 patients a normal-looking appendix, whereas in other 6 patients, it identified neither appendix nor indirect signs of acute appendicitis. A normal appendix has been detected by US during follow-up in 2 of these 6 patients. During follow-up, US finding of OI disappeared in all cases and no signs of acute appendicitis or other disease occurred. All 14 OIs were treated conservatively, with no reported complications. Conclusions: Omental infarction is an underestimated cause of abdominal pain in children accounting for 7% of patients with suspected appendicitis. Ultrasonography is a useful method for the diagnoses and to guide clinical management of OI. Conservative therapy is a safe option for the management of OI.